Efecto de tres dosis de humus y roca fosforica en tres Densidades de siembra,en repollo (Brassica Oleracea L.) en el fundo Aucaloma-UNSM - T - Rojas Rodriguez, Celustiano (2012)
This research was conducted with the objectives of determining the number of doses of vermicompost suitable for the production of cabbage in different densities, making an economic analysis of the treatments studied, seeking to improve performance and prof itability of the crop in acid soils of the farm Aucaloma owned by the Universi ty National de San Martin - Tarapoto, located in the area Aucaloma with a geographic location of 720 meters, south latitude 06 ° 20 'west longitude and 76 ° 21', 15 km from Tarapoto , following the road to San Antonio de Cumbaza, understanding of the San Roque district, province and region of San Martin Lamas. The design was a randomized complete block (RCBD) with factorial arrangement of four for three with three replications, yielding the following results: worm castings to 7000 kg ha -1 had a positive linear behavior, which made effect on the crop with respect to plant height (12.23 cm), leaf area (95.68 cm2), number of functional leaves (11.21), head diameter (11.07 cm) and crop yield (31185.67 kg ha -1). As mentioned economic analysis that all treatments were favorable earnings, ranging from a B / C of 3.21 for the T11 (0.50 X 0.40 + 7000 kg.ha -1 of vermicompost) to 4.40 for the T10 (0.50 X 0.40 + 5000 kg.ha - 1 of vermicompost). Control treatments (T4, T8 a nd T12) reached relationships B/C of 4.28 rather interesting, 4.02 and 3.82 respectively, despite having obtained lower yields per hectare and that the sale price was S/. 0.50 soles because the sizes of the heads were smaller.